Mechanical and microscopic characterization of expansive soils modified by water-soluble polymers - Fan Yang; Yong Zhao; Huanyu Dong; Huarong Wang; Wangjin Niu; Zhixia Zhao; Fuyong Song; Hang Tan (Scientific Reports)
Abstract With the advancement of ecological and environmental protection construction, the research on the modification of expansive soil using environmentally friendly polymers can make up for the harm to the ecological environment caused by traditional modification. Mechanical and microscopic properties of modified expansive soils were analyzed through indoor tests. The results showed that the liquid limit and plasticity index decreased by 52.14% and 77.36%, respectively, and the plastic limit increased by 20.83%. Maximum dry density decreased by 5.11% and optimum moisture content increased by 28.47%. The compressive and shear strength increases and then decreases with the increase of dosage, and the strength reaches the maximum when the dosage is 4%, and the vertical and lateral deformation of the specimen is the smallest. Modified soil swelling was reduced by 54.57% and swelling forces were reduced by 15–57%. The modified soil cracks developed slowly and the width of the cracks was reduced by 61.68% after the modification. Microscopy showed that no new minerals were generated after doping modifier, while hydrophilic minerals were reduced by 43.14%, and the gel film formed by hydration made the pores smaller and the structure tighter by filling and wrapping on the surface of the particles.